Suppressive effects of Levilactobacillus brevis on Fusarium-plant disease and its potential contribution to environmentally friendly agriculture - Yoshiko Nakashima; Norihito Yamauchi; Hirotatsu Murano (Biological Control)
To harmonize with sustainable practices, chemical pesticide use is being reduced globally, and more farmers are adopting environmentally friendly agricultural methods. In this context, lactic acid bacteria (LAB) have garnered increasing attention as potential biocontrol agents, biostimulants, and biofertilizers; however, the mechanisms underlying their effects remain unclear. Levilactobacillus brevis KB290, a heterofermentative bacterium that produces acetic and lactic acids, and Lacticaseibacillus paracasei KB182-SBR1202, a homofermentative bacterium that produces only lactic acid via which it suppresses Fusarium growth, both in vitro and in natural soil, are being explored for their inhibitory mechanisms. At concentrations of 101 and 106 CFU mL−1, L. brevis reduced Fusarium growth by 36 % and 100 %, respectively, whereas at concentrations of 106 CFU mL−1 L. paracasei only reduced Fusarium growth by 14 %. To understand the inhibitory mechanism, LAB were cultured in liquid media and organic acid concentrations were measured. L. paracasei produced only lactic acid, whereas L. brevis produced lactic and acetic acids. The IC50s for lactic and acetic acids were 18.4 mM and 9.72 mM, respectively. Acetic acid completely inhibited Fusarium growth, whereas lactic acid did not achieve complete inhibition at 100 mM. This suggests that acetic acid production is a key factor in Fusarium suppression. Application of L. brevis to Fusarium-contaminated soil suppressed Fusarium disease in Japanese mustard spinach (Komatsuna) for up to 14 days. Collectively, these findings suggest that L. brevis has the potential to effectively suppress Fusarium disease without the need for chemical pesticides, thereby supporting environmentally friendly agricultural practices.